Data Digitization Strategy through A Google Site-based School Data Collection Site at SMP Negeri 1 Montasik - Julian (Winaya Inspirasi Nusantara Foundation, 2023)
This research aims to examine data digitalization strategies through the Google Site-based school data collection site at SMP Negeri 1 Montasik. The research method used is descriptive research with a qualitative and quantitative approach (mixed method). Data was collected through questionnaires, interviews, and observations. The research results show that the implementation of a Google Site-based school data collection site at SMP Negeri 1 Montasik has increased data management efficiency, accelerated the data collection and processing process, and increased data accuracy. Benefits include operational efficiency, deeper data analysis, easy access to information, and better decision-making. However, this research also identified several challenges and obstacles faced, including limited staff knowledge and skills, technical and infrastructure constraints, and resistance to change among teachers and administrative staff. Based on the findings of this research, the recommendations given are to improve staff training and education in the use of school data collection sites, improve technological infrastructure, and implement effective communication programs to overcome resistance to change. Apart from that, it is also important to encourage collaboration between teachers and administrative staff, as well as carry out regular evaluation and monitoring of the implementation of the Google Site-based school data collection site. It is hoped that this research can contribute to the development of a data digitization strategy through a Google Site-based school data collection site at SMP Negeri 1 Montasik and provide insight to other schools about the benefits, challenges, and recommendations related to using this strategy.